State Bank of India's Osaka experience - Salwan, Prashant; Bhatta, N. M. K.; Jain, Himanshu (London : Neilson Journals Publishing, 2018)
Institutional reforms in emerging economies coupled with the globalization of markets and production, have influenced the banking industry of these economies hugely. To cope with competition and to increase revenues, banks have internationalized. The State Bank of India (SBI) recorded 27% of its profits (FY 2017) coming from international operations. Its internationalization efforts have, however, not been without challenges ... one being its entry into Japan. SBI created an overseas branch in Osaka in 1984 with the aim of servicing Indian nationals who had moved there for work. But by 1989, the accumulated losses had risen to JPY 434.97 million (USD 4 million approx.) with a bad debt provision of JPY 244.07 million (USD 2.4 million approx.). The situation remained bad for a decade. SBI management had to find the reasons for this and then devise a plan of what to do about it. Students learn about how Indian banks have internationalised, and how SBI coped with and adjusted to a very foreign market and culture. Lessons learnt are applicable to other emerging nations' banks as they seek to expand overseas.
Originally Published In Salwan, P., Bhatta, N., & Jain, H. (2018). State Bank of India's Osaka Experience. Journal of International Business Education, 13(1), 403-414. JIBE13-0CS9.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; State Bank of India; Banks and banking -- Japan -- Case studies